TEKANAN DAN DUKUNGAN SEBAGAI ANTESEDEN WORK-FAMILY CONFLICT; STUDI PADA PEGAWAI BERSEKOLAH DI WILAYAH DIY - Widjajani, Susi (Jurnal Analisis Bisnis Ekonomi, 2009)
The purpose of this research is to examine the relationship between job stress, job support, family support, and  family stress , with  work-family conflict. Variabel in this research were measured via survey of 226 student Magister Management on the University in the DIY.  Multiple Regression Analysis  were used to examine the effect to antecedent  of work-family conflict.  Result showed in this research  that job stress, family support, and family stress significantly related to work-family conflict, but no significantly related with family support.  . Finally, these results have an important implication to managers in scheme work-family orient.